2000
DOI: 10.2105/ajph.90.2.223
|View full text |Cite
|
Sign up to set email alerts
|

Mortality from invasive pneumococcal pneumonia in the era of antibiotic resistance, 1995-1997

Abstract: OBJECTIVES: This study examined epidemiologic factors affecting mortality from pneumococcal pneumonia in 1995 through 1997. METHODS: Persons residing in a surveillance area who had community-acquired pneumonia requiring hospitalization and Streptococcus pneumoniae isolated from a sterile site were included in the analysis. Factors affecting mortality were evaluated in univariate and multivariate analyses. The number of deaths from pneumococcal pneumonia requiring hospitalization in the United States in 1996 wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 516 publications
(63 citation statements)
references
References 48 publications
2
60
0
1
Order By: Relevance
“…In contrast to previous studies that found no difference in mortality, both Metlay et al and Feiken et al demonstrated that there was an increased risk of mortality among persons infected with nonsusceptible and resistant S. pneumoniae (34,35). Metlay et al found that in-hospital mortality was significantly increased among cases with PNSP bacteremic pneumonia compared to those with penicillin-susceptible S. pneumoniae (relative risk, 2.1; 95% confidence interval, 1.0 to 4.3) (34), while in the study by Feiken et al, mortality was significantly increased in U.S. persons infected with pneumococci with penicillin MICs of Ն4.0 g/ml after the fourth day of hospitalization (35).…”
Section: Impact Of Antimicrobial Resistancementioning
confidence: 63%
See 2 more Smart Citations
“…In contrast to previous studies that found no difference in mortality, both Metlay et al and Feiken et al demonstrated that there was an increased risk of mortality among persons infected with nonsusceptible and resistant S. pneumoniae (34,35). Metlay et al found that in-hospital mortality was significantly increased among cases with PNSP bacteremic pneumonia compared to those with penicillin-susceptible S. pneumoniae (relative risk, 2.1; 95% confidence interval, 1.0 to 4.3) (34), while in the study by Feiken et al, mortality was significantly increased in U.S. persons infected with pneumococci with penicillin MICs of Ն4.0 g/ml after the fourth day of hospitalization (35).…”
Section: Impact Of Antimicrobial Resistancementioning
confidence: 63%
“…This finding was also documented by Plouffe et al among pneumococcal bacteremia cases in 10 adult care hospitals in Franklin County, OH, but those authors found that the duration of hospitalization was significantly longer for patients with penicillin-nonsusceptible S. pneumoniae (PNSP) than for those with penicillin-susceptible disease (15.8 days versus 12.1 days; P ϭ 0.05) (33). In contrast to previous studies that found no difference in mortality, both Metlay et al and Feiken et al demonstrated that there was an increased risk of mortality among persons infected with nonsusceptible and resistant S. pneumoniae (34,35). Metlay et al found that in-hospital mortality was significantly increased among cases with PNSP bacteremic pneumonia compared to those with penicillin-susceptible S. pneumoniae (relative risk, 2.1; 95% confidence interval, 1.0 to 4.3) (34), while in the study by Feiken et al, mortality was significantly increased in U.S. persons infected with pneumococci with penicillin MICs of Ն4.0 g/ml after the fourth day of hospitalization (35).…”
Section: Impact Of Antimicrobial Resistancementioning
confidence: 91%
See 1 more Smart Citation
“…1 An estimated 5.6 million cases of CAP occur annually in the United States, 2 with 1.2 million patients hospitalised and an inpatient mortality rate of 5.8%. 3 Streptococcus pneumoniae accounts for about 50% of all cases of CAP requiring admission to hospital.…”
Section: Introductionmentioning
confidence: 99%
“…Streptococcus pneumoniae is the most important bacterial pathogen implicated in community-acquired invasive and non-invasive infections and is associated with significant morbidity, mortality and financial expenditures [1,2,3]. Timely and appropriate empirical antimicrobial treatment is critical to improve outcome and reduce mortality rates [4,5].…”
Section: Introductionmentioning
confidence: 99%